1992
DOI: 10.1177/0146167292185006
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Causal Attributions: The Revised Causal Dimension Scale (CDSII)

Abstract: Although attribution theory continues to be a fertile area of social psychological research, much of the extant literature has suffered from questionable measurement of the constructs of interest. This is especially true in the case of assigning causal attributions placement in theorized dimensional space. Russell's (1982) Causal Dimension Scale represented an important development toward more precise measurement of causal dimensions; however, it has been criticized on a number of fronts. The present report pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
373
1
23

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 441 publications
(428 citation statements)
references
References 30 publications
20
373
1
23
Order By: Relevance
“…Shimodera et al (2002) showed the sensitivity with the FMSS was 66.7% and the specificity was 95.2% in a sample of Japanese families of patients with mood disorders. (McAuley, Duncan, & Russell, 1992). The scale includes three items.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shimodera et al (2002) showed the sensitivity with the FMSS was 66.7% and the specificity was 95.2% in a sample of Japanese families of patients with mood disorders. (McAuley, Duncan, & Russell, 1992). The scale includes three items.…”
Section: Methodsmentioning
confidence: 99%
“…Causal Dimension Scale (CDS-II) is a self-report measure of how people perceive causes of particular situations (McAuley, Duncan, & Russell, 1992). The scale includes three items.…”
Section: Attributions-thementioning
confidence: 99%
“…Causal Dimension Scale II (CDS II;McAuley, Duncan & Russell, 1992). This scale shows whether the causes attributed by alcoholics to their periods of abstinence and relapses are internal/external, stable/unstable and controllable/uncontrollable.…”
Section: Methodsmentioning
confidence: 99%
“…Scale II (CDSII; McAuley, Duncan & Russell, 1992), with instructions modified to reflect causes of adherence to exercise. The CDSII was a 12 item test, each item with numbers one through nine with opposing descriptions as anchors which were unique to each item.…”
Section: Attributions the Attributions Measurement Used Was The Causmentioning
confidence: 99%
“…It should be noted that the CDSII divided the controllability dimension as described previously (Weiner, 1992) into two dimensions: personal control and external control (McAuley, Duncan & Russell, 1992). Personal control refers to the ability of the person to control the primary cause (controllable or uncontrollable), while external control refers to the ability of others to control the primary cause (controllable or uncontrollable).…”
Section: Attributions the Attributions Measurement Used Was The Causmentioning
confidence: 99%